Energy and exergy analyses of a portable air conditioner system. Issue 1 (January 2021) - López, R; Vaca, M; Terres, H; Lizardi, A; Chávez, S; Lara, A
Abstract: In this analysis the main objective is to evaluate the thermodynamic behavior of a portable air conditioning system. The power is 4, 103 kW. To achieve this, the device was implemented with pre-calibrated thermocouples, taking care that there was always a proper contact with the pipes in order to minimize the differences between the measurement and the actual value. The ESS software and the coolant thermodynamic diagram were used to determine the value of the properties at the considered points. The refrigerant used by this device is the R 410A. Although the first law of thermodynamics can be used to assess the energy consumption, it makes no distinction between quantity and quality of energy. Energy analysis provides only the amount of supplied energy. Exergy analysis provides the maximum useful work that can be obtained by a system that is in balance with the environment. The COP (Coefficient of Performance), turned out to be 7.35, which is acceptable for this type of device. The exergetic efficiency was 4.17. Finally, the hot air flow coming from the condenser was 3.15 kW, this value is significant and will be used in some drying application.